Regional-level estimation of expected years of life lost attributable to overweight and obesity among Mexican adults - Efrén Murillo-Zamora; Raúl García-Ceballos; Iván Delgado-Enciso; Raquel Garza-Guajardo; Oralia Barboza-Quintana; Irám P. Rodríguez-Sánchez; Oliver Mendoza-Cano (Taylor & Francis Group, 2016)
Background: Excess body weight has become a major public health problem worldwide, and the burden of overweight and obesity was calculated in this work from a health economics perspective. Objective: To estimate the burden of disease attributable to overweight and obesity among males and females aged 20 years and older using years of life lost (YLL) and age-standardized YLL rates (ASYLL), and to rank the leading causes of premature death. Design: A cross-sectional study took place (2010-2014) and 6,054 deaths were analyzed. Thirteen basic causes of death associated with overweight or obesity were included. The population attributable fraction (PAF), YLL, and ASYLL were calculated. Results: The overall burden attributable to overweight and obesity was 36,087 YLL, and the estimated ASYLL per 10,000 persons was 1,098 and 1,029 in males and females, respectively. Type 2 diabetes mellitus was the main cause of premature death (males, 968 ASYLL; females, 772 ASYLL). Conclusions: Overweight and obesity are major risk factors of chronic diseases that are main causes of premature death in the study population. Strategies for preventing overweight and obesity may decrease the incidence and mortality associated with these non-communicable diseases. ASYLL seems to be an indicator that is particularly well adapted to decision-making in public health.